2020
DOI: 10.29309/tpmj/2020.27.06.3508
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical profile of obese and overweight children at a Tertiary Care Hospital.

Abstract: Objectives: Childhood and adolescent obesity is increasing especially in developing countries like Pakistan. It seem to affect most socio-economic classes as well as all ethnicities and geographies. We planned this study to analyze the clinical and biochemical profile of obese as well as overweight children at a tertiary care hospital for the existence of metabolic syndrome. Study Design: Cross sectional study. Setting: Department of Pediatrics Medicine, Children Hospital Chandka Medical College / Shah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…11,14 The most common physical finding of our study was Acanthosis Nigricans followed by hypertension which was also observed by Khuhro et al in their study. 15 Acanthosis Nigricans has been the most common skin manifestation in obese children and has been linked to insulin resistance and high risk to type 2 diabetes mellitus (T2DM). 16,17 Therefore early recognition of this symptom can result in screening for complications of obesity in children.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 The most common physical finding of our study was Acanthosis Nigricans followed by hypertension which was also observed by Khuhro et al in their study. 15 Acanthosis Nigricans has been the most common skin manifestation in obese children and has been linked to insulin resistance and high risk to type 2 diabetes mellitus (T2DM). 16,17 Therefore early recognition of this symptom can result in screening for complications of obesity in children.…”
Section: Discussionmentioning
confidence: 99%